MicroRNA-23a promotes colorectal cancer cell migration and proliferation by targeting at MARK1. (10th June 2019) - Tang, Xiaoli; Yang, Meiyuan; Wang, Zheng; Wu, Xiaoqing; Wang, Daorong
Abstract: The functional role of microRNA-23a in tumorigenesis has been investigated; however, the exact mechanism of microRNA-23a (miR-23a) in colorectal cancer development has not been fully explored. In the present study, we aimed to investigate the molecular functional role of miR-23a in colorectal carcinogenesis. Quantitative real-time polymerase chain reaction was conducted to investigate the expression level of miR-23a in tissue samples and cell lines (HCT116 and SW480). CCK-8, colony formation and Transwell assay were used to explore the role of miR-23a in cell proliferation and migration. Dual luciferase reporter assay was used to identify the direct binding of miR-23a with its target, MARK1. Western blot analysis was used to analyze the expression level of MARK1, as well as a confirmed miR-23a target gene, MTSS1, in miR-23a-mimic and miR-23a-inhibit groups. Rescue experiments were conducted by overexpression of MARK1 in miR-23a-mimic-transfected cell lines. The results showed that miR-23a was highly expressed in colorectal cancer tissue and cell lines. MiR-23a could promote proliferation and migration of colorectal cancer cell lines. MARK1 was a direct target of miR-23a and the expression level of MARK1 was down-regulated in miR-23a-mimic-transfected cell lines but up-regulated in miR-23a-inhibit-transfected cells. Overexpression of MARK1 could partly reverse the cancer-promoting function of miR-23a. Our results suggested that miR-23a promotes colorectal cancer cell proliferation and migration by mediating the expression of MARK1. MiR-23a may be a potential therapeutic target for colorectal cancer treatment.